Executable MBSE approach with illustration of a satellite engagement mission design - Rangel, Diego Custódio (2021)
Model-based systems engineering (MBSE) is becoming the industry standard for systems engineering activities. To avoid design flaws and reduce rework and cost, the descriptive models developed using the modern MBSE tools need to be integrated with other engineering discipline models. The co-simulation approach envisioned for current MBSE tools facilitates the use of external solvers to solve mathematical expressions within the model. Indeed, integrating complex simulations to couple descriptive and physics-based models is a challenging task requiring quite a few adjustments to both models to produce an executable MBSE model. This thesis aims to enhance the use of one of the most advanced MBSE tools—Cameo Systems Modeler (CSM)—to be able to execute high-fidelity models of combat systems running in the Simulink development environment. Such an executable model should greatly improve and enhance feasibility of analysis of any combat mission during early system design phases. As an example, this thesis models a co-orbital engagement (COE) of two satellites and walks through all steps of the CSM-Simulink integration process. A shared workspace of MATLAB serves as a critical enabler for dealing with the data transfer. The thesis provides an example of how the developed integrated model can be used to analyze the COE mission and explore an effect of reshaping the design space via varying a set of mission requirements.